Problems of implementation of World Food Program in relation to utilization and acceptability of commodities at the Mindanao Institute of Technology - Clemente, Maclara Saavedra
This study was conducted at the Mindanao Institute of technology (MIT) to identify problems related to the utilization and acceptability of food items donated by the World Food Program. The sample consisted of 435 college students and 74 employees. Information from the respondents was solicited through interview sheet and questionnaire. Aside from MIT, the problems of implementing the WFP projects at the Central Luzon State University (CLSU) and the Mindanao State University (MSU) were also studied. Among the three institutions, only MIT has an on-going project at present. Students were generally using the commodities as food. Canned dried egg was most utilized as food because of taste, positive effect on health and was conveniently used ingredient in various food preparations. Pulses were least utilized as food because of the inconvenience in cooking. Among the subjects, food utilization was related to such factors as age, sex, province of origin, year in college, course, and money spent for food. Age, province of origin and money spent for food were not found related to food utilization. More females were utilizing as food wheat flour, dried skim milk, dried fruit, and canned fish. For bulgur wheat, there were more males than females who did not eat this commodity. Upper class men (3rd to 5th year) had a higher food utilization of wheat flour than the students in the lower years (1st to 2nd year). H.E. students consumed pulses much more than students in the other curricular offerings. In case of the employees, 96% on the average utilized the commodities as food. Among the commodities, canned butter had the highest food utilization (100%) because it was conveniently used as an ingredient in various food preparations. Although canned cheese was eaten as is and used as an ingredient in various food preparations, the food utilization was least because of odor. Factors mentioned to determine utilization of food items were number of children and amount of money spent for food per caput a month. The number of children of employees dis not seem to affect the food utilization of the commodities. There was a tendency for employees to utilize the commodities fully as food when the amount of money spent for food is small. In terms of acceptability, students gave canned dried egg the highest rating because of taste and positive effect on health and pulses the lowest rating because of the inconvenience in cooking. Employees gave canned cheese the highest rating because of cost and taste while dried fruit had the lowest rating because of the taste and texture. There was a direct relationship between utilization and acceptability of the WFP commodities among students. For employees, food utilization and acceptability had an inverse relationship. Problems initially encountered in implementing the WFP project at MIT were transportation, storage, and the use of the commodities for purposes other than food. Illegal disposal and pilferage in the school's warehouse were the problems encountered at CLSU. At MSU, the administration cited unacceptability of unfamiliar food items as the major problem in implementing the project.